Leave None to Claim the Land. A Malthusian Catastrophe in Rwanda? - Marijke Verpoorten (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
More than 200 years after its first publication, the Malthusian thesis is still much debated, albeit in a modified firm. Rather than predicting a global catastrophe, most neo-Malthusians stress the local character of the relationship between population pressure , natural resource scarcity, and conflict as well as its dependency on the socio-political and economic context. This softened version of Mathus' thesis has received little emphirical support in cross-country studies. In contrast, a number of sub-national analyses have provided some evidence for local conditional Malthusian catastrophes, although 'catastrophe' is a big word since these studies have largely focused on low-intensity violence. This article adds to the small body of sub-national studies, but focuses on a high-intensity conflict, the Rwandan genocide. In particular, it provides a meso-level analysis of the relation between population pressure and the intensity of violence measured by the death toll among the Tutsi across 1,294 small administrative units. The results indicate that the death toll was significantly higher in localities with bothhigh population density and little opportunity for young men to acquire land. On the one hand, this finding can be interpreted as support for the neo-Malthusian thesis. On the other hand, it is possible that another mechanism played, i.e. in densely populated areas it may have been relatively easy for the elite to mobilize the population, because of dependency relations through the land and labor market. Alternatively, in densely populated areas, there may have been more lootable assets, and the violence may have been opportunistic rather than driven by need or by fear.
Keywords: 330